(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2017)
Nowadays, sustainability has become one of the main aspects in architecture and urbanism. Limited land, space usage efficiency, public area occupancy by private sector and energy efficient are few examples of various factors that cause the temporality. Space temporality, instead of temporality in time and users, both planned and unplanned, becomes an interesting issue to be explored further. Literature studies and empirical observation are used in this article as reference to redefine the concept of ‘space’, in regards to its adaptability and flexibility in sustainable architecture. This research aims to construct a design guide of a temporal space (such as classifications, characters, and some other elements). There are several design guidelines that can help architect in designing an adaptable and flexible space or building. Space, user, and time (both adaptability and flexibility) are the key factors for a sustainable design.